2017
DOI: 10.4103/ijmy.ijmy_19_17
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol for prophylaxis against antituberculosis therapy-induced liver disorders among naïve patients with pulmonary tuberculosis: A randomized, comparative study

Abstract: Adjuvant cholecalciferol supplementation may be protective against ATT-LD without extra adverse effects. Before recommending the routine use of cholecalciferol supplementation for prevention of ATT-LD, larger scale studies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Current study design was based on earlier studies represented that free 25(OH)D showed higher correlation with the actual vitamin D deficient states than 25(OH)D (23). Similar to some earlier studies, female patients were predominant sex group and most of patients belonged to the age group 40–50 (n=48, 60%) (1, 20). Joint manifestations proportion were higher than previous reports (14%–36%) (24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Current study design was based on earlier studies represented that free 25(OH)D showed higher correlation with the actual vitamin D deficient states than 25(OH)D (23). Similar to some earlier studies, female patients were predominant sex group and most of patients belonged to the age group 40–50 (n=48, 60%) (1, 20). Joint manifestations proportion were higher than previous reports (14%–36%) (24).…”
Section: Discussionsupporting
confidence: 89%
“…Thereby, the study was approved by the Ethics Committee of Shahid Beheshti medical sciences university (SBMU 1.REC.1393.71). An expert methodologist estimated the study population size due to statistics guidelines (19, 20).…”
Section: Methodsmentioning
confidence: 99%
“…From 2011 to 2020, publications per year were nearly stationary but no reported publications in 2021. Near half of publications were case reports (185)(186)(187)(188)(189), but the others were variety of randomized controlled trials (190,191), prospective (192,193), retrospective (194,195), cohort (196)(197)(198) and observational studies studying the presentation, causes, diagnosis and outcomes of DILI but no studies in liver transplantation in DILI and toxic liver patients.…”
Section: Toxic and Drug Induced Liver Injurymentioning
confidence: 99%